An open minded look at fashion photography - Howard, Duane (Bloemfontein: Central University of Technology, Free State, 1999)
This script is divided up into four sections. The first section covers some of the pioneers of fashion photography as well as a few other photographers which helped develop the photographers style, not necessarily through their work but through their interpretation of the subject. The third and fourth sections contain the images of the famous photographers as well as the authers own work, these two sections are divided into Gallery A and Gallery B.
Thesis
Keywords: Photographers; Fashion photography; Photographs